Second meeting report of the Food Safety Technical Working Group launch under One Health Partnership Framework - Vietnam One Health Partnership for Zoonoses (International Livestock Research Institute, 2024)
The report presents a summary of updates on progress in implementing food system transformation in Vietnam; the food poisoning situation and work to ensure food safety and prevent food poisoning; the food safety group's communication activities in 2024; and food safety implementation activities by government, private and international partners.